Incidence and Severity of Lymphoedema following Limb Salvage of Extremity Soft Tissue Sarcoma. (20th November 2011) - Friedmann, Daniel; Wunder, Jay S.; Ferguson, Peter; O'Sullivan, Brian; Roberge, David; Catton, Charles; Freeman, Carolyn; Saran, Neil; Turcotte, Robert E.
Abstract : Background and Purpose . Lymphoedema is a serious complication following limb salvage for extremity soft tissue sarcomas (STSs) for which little is known. We aimed to evaluate its incidence, its, severity and its associated risk factors. Material and Method . Patient and tumor characteristics, treatment modalities and complications and functional outcomes (MSTS 1987, TESS), and lymphoedema severity (Stern) were all collected from prospective databases. Charts were retrospectively abstracted for BMI and comorbidities. Results . There were 289 patients (158 males). Mean age was 53 (16–88). Followup ranged between 12 and 60 months with an average of 35 and a median of 36 months. Mean BMI was 27.4 (15.8–52.1). 72% had lower extremity tumors and 38% upper extremity. Mean tumor size was 8.1 cm (1.0–35.6 cm). 27% had no adjuvant radiation, 62% had 50 Gy, and 11% received 66 Gy. The incidence of lymphoedema was 28.8% (206 none, 58 mild, 22 moderate, 3 severe, and 0 very severe). Mean MSTS score was 32 (11–35) and TESS was 89.4 (32.4–100). Radiation dose was significantly correlated with tumor size > 5 cm (P = 0.0001 ) and TESS score (P = 0.001 ), but not MSTS score (P = 0.090 ). Only tumor size > 5 cm and depth were found to be independent predictors of significant lymphoedema. Conclusion . Nine percent of STS patients in our cohort developed significant (grade ≥ 2 ) lymphoedema. Tumor size > 5 cm and deep tumors were associated with an increased occurrence of lymphoedema but not radiation dosage.